Database Implementation to Improve Transaction Recording Efficiency of Soeka Dimsum MSMEs Using Entity Relationship Charts - Jamilah, Adiba Alia; Ambarwati, Rini; Setiawan, Tanisha Avriani Putri; Ullinnuha, Maitsa; Junianto, Dimas (Jurnal Multidisiplin Indonesia, 2025)
This study examines the application of Microsoft Access as a recording system in Soeka Dimsum MSMEs which previously still used the manual method. The purpose of the study is to show how the design of an Entity Relationship Chart-based database can improve efficiency in managing financial data, stock of goods, and revenue according to the required period. The research method used was qualitative descriptive through direct data collection at MSME locations, observation of the recording process, and interviews with business owners. The results of the study show that manual recording makes it difficult for owners to obtain data in real-time and in a structured manner. The implementation of Microsoft Access has proven to be able to simplify the recording flow so that it is more accessible and ultimately increases the efficiency of the data collection process in Soeka Dimsum MSMEs. This practical database solution enables MSME owners to make faster, data-driven business decisions while significantly reducing time spent on administrative tasks, thereby allowing more focus on core business operations and growth strategies.